2018
DOI: 10.1101/443804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrophilic PROTACs that degrade nuclear proteins by engaging DCAF16

Abstract: Ligand-dependent protein degradation has emerged as a compelling strategy to pharmacologically control the protein content of cells. So far, only a limited number of E3 ligases have been found to support this process. Here, we use a chemical proteomic strategy to discover that DCAF16 -a poorly characterized substrate recognition component of CUL4-DDB1 E3 ubiquitin ligases -promotes nuclear-restricted protein degradation upon modification by cysteine-directed heterobifunctional electrophilic compounds.Conventio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
101
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 25 publications
2
101
0
Order By: Relevance
“…More recently, the applicability of PROTACs has been broadened to include multi-functional proteins (e.g., TRIM24 [34], SMARCA2 [35] tau [36,37]), and HaloTag7-fused proteins for chemical genetics [38]. In parallel, the space of E3 ligases used has also expanded: whereas early studies focused exclusively on CRBN and Von Hippel-Lindau protein (VHL), more recent work has used E3 ligases MDM2 [39], IAP [40], RNF4 [41], βTRCP [42], parkin [42], and DCAF16 [43].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the applicability of PROTACs has been broadened to include multi-functional proteins (e.g., TRIM24 [34], SMARCA2 [35] tau [36,37]), and HaloTag7-fused proteins for chemical genetics [38]. In parallel, the space of E3 ligases used has also expanded: whereas early studies focused exclusively on CRBN and Von Hippel-Lindau protein (VHL), more recent work has used E3 ligases MDM2 [39], IAP [40], RNF4 [41], βTRCP [42], parkin [42], and DCAF16 [43].…”
Section: Introductionmentioning
confidence: 99%
“…Chemoproteomic profiling, particularly where electrophilic fragments react with cysteine, has repeatedly been used to elucidate novel E3 ligases, often leading to the rapid design of PROTACs that covalently bind to their ligases. [28][29][30] (However, it has recently been suggested that such covalent binders are perhaps ill-suited for PROTACs, 31,32 although this finding has itself been questioned. 33 ) Multiple independent research groups have recently developed photoactivated PROTACs, [34][35][36][37] and novel experimental diagnostic techniques [38][39][40] will continue to afford additional insight with both greater accuracy and throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Because the N-terminal region of RNF114 that includes C8 is intrinsically disordered, structure-guided ligand discovery and optimization was not possible thus requiring unbiased approaches to ligand discovery. Activity-based protein profiling (ABPP)-enabled covalent ligand screening has been previously used to discover novel covalent recruiters against E3 ligases RNF4 and DCAF16 (Ward et al, 2019;Zhang et al, 2019) and has also facilitated ligand discovery against cysteines targeted by covalently-acting natural products (Grossman et al, 2017). Using this technique, we were able to discover fragments that could be used to functionally replace nimbolide as the covalent E3 ligase recruitment module in fully functional degraders against several oncology targets.…”
Section: Introductionmentioning
confidence: 99%